(untitled) (Ibrahim Cardiac Medical Journal, 2024)
Background & objective: Anaemia is the most significant disorder of the blood. Many researchers have developed the concept of using medicinal plants as an alternative source of treatment for anaemia with fewer side effects. Aloe vera, being a medicinal plant, is popularly used as a natural drug in haematological disorders. The present study was intended to observe the effects of Aloe vera gel on red blood cell parameters in phenylhydrazine (PHZ)-induced anaemic Wistar albino rats. Methods: This Experimental study was conducted in Dhaka Medical College, Dhaka from July 2021 to June 2022. A total of 24 healthy Wistar albino rats were selected for the study. After procurement, the rats were initially kept in a standard laboratory condition on a 12/12-hour light/dark cycle for 14 days of acclimatization before 21 days of the experiment. All the rats had free access to basal diet and normal saline during the period of acclimatization and experiment. After acclimatization for 14 days, the rats were divided into three groups-Group A (baseline control group, n = 8), Group B (PHZ-treated group, n = 8), and Group C, the Experimental Group (PHZ-induced and Aloe vera gel treated group, n = 8). To induce anaemia, Group B and Group C received intraperitoneal injection of PHZ at a dose of 0.5 ml/100 g body weight on days 1, 3, 5 and day 7. Moreover, the experimental group (Group C) received Aloe vera gel orally at a dose of 0.6 ml/kg body weight from Day 8 to Day 21. On day 22, rats were sacrificed to test their blood samples for haematologic variables (RBC count, Hb conc., and PCV) and haematological indices (MCV, MCH and MCHC). Result: All the haematological parameters and indices were almost similar among the study groups at baseline (on Day 1). On Day 8, rats of groups B and C demonstrated a drastically reduced count of RBC (2.66 ± 0.53 and 2.69 ± 0.52 million/μl respectively) compared to the rats of group A (8.16 ± 0.76 million/μl). On Day 22, the RBC count in rats of Group C staggeringly increased to 7.63 ± 0.64 million/μl; however, the RBC count in rats of Group B remained almost the same as was found on Day 8. A significant decrease in Hb conc. and PCV in PHZ-induced control on Day 8 compared to that on Day 1 was also observed. The mean MCV in all the study groups on Day 1 was around 50 fl, which abnormally increased to 85 and 87 fl in Groups B and C respectively on Day 8. On Day 22, Group B further exhibited an increase in MCV to > 87 fl. Meanwhile, the MCV in Group C (Aloe vera-treated group) favourably decreased to 55 fl. On the 8th Day of intervention, the MCH level significantly decreased in Groups B and C. Although no significant change in MCH was observed in Group B from Day 8 to Day 22, group C demonstrated a significant increase in the mean MCH to nearly 18 pg during the same period. The mean MCHC significantly dropped to < 23% in Groups B and C on Day 8 from the baseline figure of 34%. While no significant change in MCHC was evident in Group B from Day 8 to Day 22, it significantly improved to about 28% in Group C during the same period. Conclusion: From the study, it can be concluded that Aloe vera has significant erythropoietic potentials which result in the improvement of red blood cell parameters (RBC count, Hb conc., PCV, MCV, MCH and MCHC) in PHZ-induced anaemic rats. Ibrahim Card Med J 2023; 13 (1&2): 40-46